PENGARUH LABEL HALAL PADA PRODUK DALAM KEMASAN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN: Studi pada Produk Kecantikan di Supermarket Chandra dan Ramayana Kota Bandar Lampung - M. Yusuf Bahtiar (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2019)
The people of Bandar Lampung City are known as religious communities with Islam as the religion of the majority of the population. Its population structure is more Muslim women cause this city to become a market for beauty products that are so potential and become the target of domestic and foreign producers. The formulation of the problem which is the focal point of this research is how the halal label and the price of beauty products can influence the decision to buy a beauty product considering that the products available on the market do not all have a halal logo from the Indonesian Ulama Majlis. This study uses a qualitative (naturalistic) approach which is believed to be able to explain the existing phenomena more comprehensively in seeing the effect of halal labels on packaged products and prices on purchasing decisions that occur in beauty products at Chandra Supermarket and Ramayana Supermarket in Bandar Lampung City. The results showed that the factors considered in the first decision making were the quality and perception of the quality of beauty products, the suitability of individuals with products and information/referrals from 3rd person and advertisements on various media. Information on the following considerations is the brand and prestige of beauty products, product prices and halal status.Keywords: halal labels, prices, purchasing decisions.